Epidermoid Causing Ischemic Stroke in the Brainstem - Raghvendra Ramdasi; Amit Mahore; Abhijeet Kulkarni; Vithal Rangarajan; Manoj Patil; Juhi Kawale (Case Reports in Neurological Medicine)
Intracranial tumors may rarely cause stroke. We report an epidermoid cyst causing stroke in a pediatric patient. We have also reviewed the literature and pathogenesis of stroke caused by intracranial tumors.